Handbook of marriage counseling - Callahan, Constance; Ard, Ben (California: Science and Behavior Books, 1976)
Contents: Overview. The place of philosophy and values in marriage couseling. Theoretical issues and viewpoints. Conjoint marriage couseling. Group marriage couseling. Premarital couseling. Couseling regarding sexual. Proffesional issues and thics. Divorce couseling. Technical assitance for the marriage and family counselor
Includes bibliographical references and index
Keywords: Familia - Matrimonio